(untitled) (Research, Society and Development, 2022)
This study aims to measure the main effects of the New Coronavirus pandemic on the behaviors and eating habits of Brazilian university students. This is a descriptive research with a quantitative approach. It was carried out voluntarily, in a virtual environment, through an anonymous online questionnaire (Google forms) covering questions about eating behavior, food frequency and the use of antidepressant medications during the COVID-19 pandemic period. 268 participants were evaluated, who were mostly university students in the area of health sciences (57.7%), most of them from public institutions (66.3%), between the fifth and eighth period. It was identified the presence of feelings of sadness or frustration because of body weight (50%), desire to eat in moments of anxiety, worry and tension (52.6%). Quarantine was cited as a factor for worsening quality of life (47.8%), in which they found it difficult to follow their usual routine (82.1%). Concern about fitness generated a feeling of disadvantage (51.1%), leading to reflection on dieting (44.4%) and exercising (83.6%). Regarding weekly food frequency, university students reported a high consumption of fresh or minimally processed foods (67.47%), an average percentage of 52.42% for processed foods and a lower frequency for ultra-processed foods (47.13%). Most reported not using antidepressants (85.4%). The pandemic reflected negatively on self-perception of body image and eating behavior. Significant consumption of antidepressant drugs was not identified.